Endo and Exo Diels-Alder Adducts: Temperature-Tunable Building Blocks for Selective Chemical Functionalization - Discekici, Emre H.; St. Amant, Andre H.; Nguyen, Shay N.; Lee, In Hwan; Hawker, Craig J.; Read De Alaniz, Javier (Journal of the American Chemical Society, 2018)
The development and application of a novel endo furan-protected maleimide building block is reported. The endo isomer undergoes deprotection at temperatures ∼50 °C below the exo derivative. This enables a simple and powerful approach to quantitatively and selectively introduce functional maleimide groups via temperature modulation.
Keywords: Building blockes; Chemical functionalization; Deprotection; Development and applications; Diels Alder Adducts; Endo isomers; Maleimide group; Temperature modulation